Bioprospecting Marine Endophytic Fungi from Buton Island: Antibacterial Activity and Cellulase Production for Sustainable Blue Economy - Isti'anah, Ismi -; Tarman, Kustiariyah; Lee, Wen-Chien; Suseno, Sugeng Heri; Nugraha, Roni; Effendi, Irzal; Nurbayasari, Rodiah; Maulana, Riyan (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
Marine-derived endophytic fungi represent an underexplored reservoir of biologically active metabolites and enzymes with industrial relevance. This study investigated the fungal diversity associated with seaweed, seagrass, and mangrove leaf tissues collected from Buton Island, Southeast Sulawesi, with particular emphasis on antibacterial properties and cellulolytic activity. Thirty-two fungal isolates were successfully recovered and characterized based on morphological features. Antibacterial assays against Vibrio harveyi showed that several isolates, notably WB 1-2, WB 6-2, and SM 27-2, produced clear inhibition zones ranging from 11 to 13 mm, demonstrating notable antibacterial efficacy. Among all isolates, Aspergillus terreus (WB 1-2) exhibited the highest cellulase activity and was therefore selected for further enzymatic evaluation. The crude cellulase displayed maximum activity at pH 4 and a temperature of 70 °C. Hydrolysis products were qualitatively analyzed using HPLC, confirming the presence of glucose. These results highlight the dual potential of marine endophytic fungi as sources of antibacterial agents and thermostable cellulases. This work lays the groundwork for future development of eco-friendly enzyme production and marine-based antimicrobial resources, supporting sustainable biotechnological innovation within the blue economy framework.